Biodigestor em pequenas propriedades familiares e o benefício para a sustentabilidade - Salzer, Elisiane (2018)
The family farmer's permanence in the field, because of their great importance in world food production, is of paramount importance, and the search for a better quality of life, correct disposal of waste and value added to production are key factors in the development of the activity. Faced with these factors, the present study aims to verify how the implantation and use of a biodigester in small family farms benefits sustainability. To answer the research problem and to meet the proposed objectives the methodology used was qualitative, the objectives being characterized as exploratory and descriptive research and the procedures as field and bibliographic research. The data were obtained by means of an on-site visit to the properties of the municipality of Seara-SC that have the family biodigester installed, with questionnaires applied to ten producers and to the technician responsible for the implementation of the family biodigester in the State of Santa Catarina, and another questionnaire applied to six public managers of the municipalities that make up the western microregion of Paraná. After analyzing the data, we identified the benefits of installing the family biodigester in Seara-SC, such as improving quality of life, health, preservation of the environment, reduction of pollution, treatment of waste and financial return to Producers, that is, following the tripod of sustainability and empowering the small family property. The Producers are satisfied with the results of using the biodigester, having a return on investment of around two years, proving highly feasible, with a cost of approximately R $ 3,000.00 for the smallest model that has the capacity to generation of two cooking gas cylinders per month. For managers, the model would be a great alternative for rural sanitation that is currently almost zero in the municipalities of the West of Paraná and the development of public policies would contribute to their installation. It is concluded that the presentation of the model, through a pilot project, would encourage the installation of the biodigester by the Producers, since the innumerable benefits derived from its installation. The development of public policies for the installation of the family biodigester would benefit not only the Producers, but the population in general, because their use for rural sanitation contributes to the quality of the population's health, reducing public sector costs to health.